The Southern Pine Beetle Dendroctonus frontalis (Coleoptera: Curculionidae: Scolytinae) - Demian Gomez; Jiri Hulcr; Jeffrey Eickwort (EDIS)
The southern pine beetle (SPB), Dendroctonus frontalis Zimmermann, has been the most economically important forest insect in the pine timber industry in the southern United States. From 1960 through 1990, the bark beetle caused economic losses estimated at $900 million (Price et al. 1992). From 1998 to 2002, a four-year outbreak in the southern Appalachian Mountains affected more than 1 million acres with an economic loss of more than $1 billion (Clarke and Nowak 2009). In 2001,17,599 acres of pine forest were damaged by SPB in Florida alone, causing an estimated $38 million in damages.